The finding of crystallographic orientation dependence of hydrogen diffusion in austenitic stainless steel by scanning Kelvin probe force microscopy. (1st April 2017) - Hua, Zhengli; An, Bai; Iijima, Takashi; Gu, Chaohua; Zheng, Jinyang
Abstract: A combination of scanning Kelvin probe force microscopy (SKPFM) and electron backscatter diffraction (EBSD) has been applied to investigate the hydrogen release from thermally hydrogen-precharged type 304 austenitic stainless steel (γ-SS). The evolution of contact potential difference (CPD) well exhibits the evolution of hydrogen concentration in the near surface area. It is found for the first time that the hydrogen diffusivity in γ-SS depends on the crystallographic orientation. The hydrogen diffusion out from (001) and (101) grains is faster than from (111) grains while no obvious difference is found between (001) and (101) grains. Graphical abstract: